P031: Assessing differences between high- and low-performing resuscitation team leaders using gaze-tracking technology. (2nd June 2016) - Dashi, G.; McGraw, N.; Szulewski, A.; Egan, R.; Hall, A.; Dagnone, D.; Howes, D.
Abstract : Introduction: Crisis decision-making is an important responsibility of the resuscitation team leader but a difficult process to study. The purpose of this study was to evaluate visual and behavioural differences between team leaders with different objective performance scores using gaze-tracking technology.Methods: Twenty-eight emergency medicine residents in different stages of training completed four simulated resuscitation scenarios. Participants wore gaze-tracking glasses during each station. An outside expert blinded to participant training level assessed performances using a validated assessment tool for simulation scenarios. Several visual endpoints were measured, including time, frequency, order, and latency to observation of task-relevant and task-redundant items. Non-visual endpoints included behaviours such as summarizing, verbalizing concerns, and calling for definitive treatments, among others.Results: Preliminary findings suggest significant differences between high and low performers. High performers check vitals signs faster, and look at patients and vital signs more often than low performers. Low-performing leaders display a more fixed gaze when starting a scenario. Lastly, high performers summarize, verbalize concerns, predict and prepare for future steps, and call for definitive treatment more often than low performers.Conclusion: There are significant differences between high and low-performing resuscitation team leaders in terms of their visual and behavioural patterns. These differences identify potential focus points for competency evaluations, and may direct educational interventions that could facilitate more efficient development of expertise. The potential to study crisis decision-making behaviours and performances using the methods and metrics identified, both in simulated and real-world settings, is substantial.